2020
DOI: 10.21608/mjfmct.2020.19954.1006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in amiodarone-induced pulmonary toxicity in rats and the protective effect of L-carnitine and vitamin C

Abstract: This study aims to investigate the oxidative stress role in the pathogenesis of amiodarone-induced pulmonary toxicity and to show whether antioxidants´ coadministration with amiodarone could exert any protective effect. The study was carried out on 36 Sprague-Dawley males, rats were divided into the following six equal groups, drugs were given by gastric tube every day for 7 days as follow; control group: received distilled water, amiodarone (AM) treated group: received amiodarone (100 mg / kg body weight), L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover, we found that two carnitines (decanoylcarnitine and O-octanoyl-R-carnitine) were elevated after treatment. Carnitines have been reported to suppress inflammation [25] and oxidative stress [26] and protect against lung injury [27] . Coronavirus infection can trigger ER stress and subsequent eicosanoid and cytokine storms, and then cause tissue injury [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that two carnitines (decanoylcarnitine and O-octanoyl-R-carnitine) were elevated after treatment. Carnitines have been reported to suppress inflammation [25] and oxidative stress [26] and protect against lung injury [27] . Coronavirus infection can trigger ER stress and subsequent eicosanoid and cytokine storms, and then cause tissue injury [28] .…”
Section: Resultsmentioning
confidence: 99%